2020
DOI: 10.1007/s42770-020-00320-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of anacardic acid–loaded zein nanoparticles loaded on Streptococcus mutans biofilms

Abstract: Bacterial biofilms play a key role in the pathogenesis of major oral diseases. Nanoparticles open new paths for drug delivery in complex structures such as biofilms. This study evaluated the antimicrobial effect of zein nanoparticles containing anacardic acid (AA) extracted from cashew shells of Anacardium occidentale on in vitro Streptococcus mutans biofilm formation and mature biofilms. The minimum inhibitory concentration (MIC), minimum bacterial concentration (MBC), and antibiofilm assays were performed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The formulations were obtained by nanoprecipitation of the protein according to our previously described method [ 13 ], using zein protein as a carrier and anacardic acid at 9.375 μg/mL (ZAa), the maximum loading reached. This concentration demonstrated the antibiofilm activity of ZAa against S. mutans in vitro [ 27 ]. Blank nanoparticles (ZB) were prepared in the same manner, except for the absence of drug, and used as control.…”
Section: Materials E Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The formulations were obtained by nanoprecipitation of the protein according to our previously described method [ 13 ], using zein protein as a carrier and anacardic acid at 9.375 μg/mL (ZAa), the maximum loading reached. This concentration demonstrated the antibiofilm activity of ZAa against S. mutans in vitro [ 27 ]. Blank nanoparticles (ZB) were prepared in the same manner, except for the absence of drug, and used as control.…”
Section: Materials E Methodsmentioning
confidence: 97%
“…The cumulative effect of a short-term course treatment was assessed by a subacute toxicity assay for 7 consecutive days, according to the OECD 407 protocol [ 28 ] with some modifications, justified by the low doses administered, compatible to its effective dose [ 27 ] and the potential use as mouthwash in oral biofilm diseases prevention and control. ZAa nanoparticles were administered by oral gavage daily in two doses (ZAad 1 : 2.25 μg/kg and ZAad 2 : 112.5 μg/kg) (5 animals per group), while blank zein nanoparticles (ZB) and saline solution 0.9 % were administered in a volume equivalent to the highest dose to groups of four animals, each.…”
Section: Materials E Methodsmentioning
confidence: 99%
“…The most efficient oral rinse for reducing dental plaque germs is Chlorhexidine, which is presently regarded as the gold standard antiplaque agent [ 5 ]. It has bactericidal and bacteriostatic characteristics with adequate oral cavity durability and is more efficient against S. mutans than Lactobacillus .…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al (2020) demonstrated some anti- S. mutans biofilm activity of zein nanoparticles containing AA when used before the bacterial inoculation as a pre-treatment. However, they found no difference in bacterial viability for mature biofilms treated with their compound 16 . Another study tested the effect of the compound in early biofilm formation, showing a reduction in biomass 13 , however, similarly to the study by Lima et al (2020), the related "antibiofilm" effect might correspond to the AA potent antimicrobial activity, and not an antibiofilm effect itself as no cells were growing to form biofilms.…”
Section: Discussionmentioning
confidence: 93%
“…This effect may be triggered by inhibition of bacterial enzymes and complexation with metal ions 8 , 12 . Its activity against Streptococcus mutans has been extensively explored, with a consistent high sensitivity at low concentrations 9 , 12 , 16 . Due to this strong competence to kill S. mutans, AAs have inappropriately been defined as potential “anti-cavities” agents.…”
Section: Introductionmentioning
confidence: 99%